2014
DOI: 10.1603/ec13362
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Transmission of Crop Diseases by Insect Vectors in a Landscape Context

Abstract: Theory indicates that landscape composition affects transmission of vector-borne crop diseases, but few empirical studies have investigated how landscape composition affects plant disease epidemiology. Since 2006, Bemisia tabaci (Gennadius) has vectored the cucurbit yellow stunting disorder virus (CYSDV) to cantaloupe and honeydew melons (Cucumis melo L.) in the southwestern United States and northern Mexico, causing significant reductions in yield of fall melons and increased use of insecticides. Here, we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Unfortunately, rates of inter-colony movement via robbing and drifting remain poorly characterized. Recent research suggests that robbing and drifting can result in a large amount of mite transfer especially in apiaries that contain a high density of colonies (Frey and Rosenkranz 2014). There remains, however, ambiguity in the published work linking bee drift to mite movement, with evidence that bees from heavily infested colonies do (Kralj and Fuchs 2006) or do not (Goodwin et al 2006) drift more often than their mite-free counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, rates of inter-colony movement via robbing and drifting remain poorly characterized. Recent research suggests that robbing and drifting can result in a large amount of mite transfer especially in apiaries that contain a high density of colonies (Frey and Rosenkranz 2014). There remains, however, ambiguity in the published work linking bee drift to mite movement, with evidence that bees from heavily infested colonies do (Kralj and Fuchs 2006) or do not (Goodwin et al 2006) drift more often than their mite-free counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…; Carrière et al . ). Our findings are some of the first to demonstrate that cropland cover can have a dramatic effect on local plant virus prevalence.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, Carrière et al . () showed that the amount of the landscape containing reservoir host plants positively affected the prevalence of a whitefly‐transmitted virus in melons, and the authors found 1500 m to be the most predictive scale in this system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations